WHATSAPP AND ITS USE TO IMPROVE STUDENTS’ PRONUNCIATION ABILITY - Ana Ahsana El-Sulukiyyah (FKIP Universitas Islam Jember, 2016)
Studying Pronunciation was boring with similar ways given to students. Whatsapp as a kind of technology well-known by students are believed to gain the creative and interesting learning process in pronunciation class. This research method is a CAR, conducted in two cycles. Cycle one was fail because of the large group design was not effective to gain students’ enthusiasm and improve their ability. Cycle two was successful because the students could reach the criteria of success, and gained the students’ enthusiasm. In short, Whatsapp features can improve students’ ability in pronunciation class and gain their enthusiasm in studying pronunciation. Keywords : Whatsapp, Improve, Pronunciation